A New, Depth-Based Quantitative Approach to Assessing Transformative Learning. (October 2021) - Wiley, Jennifer L.; Wiley, Kristofor R.; Intolubbe-Chmil, Loren; Bhuyan, Devi; Acheson, Kris
Transformative learning (TL) goals are becoming commonplace in higher education, continuing education, and other adult learning contexts; however, valid and reliable assessments of TL are not so common. This imbalance begs the development of assessment methods that allow for a deeper understanding of how, when, and why deep reshaping of self takes place. We believe the Beliefs, Events, and Values Inventory (BEVI) to be an effective quantitative measure of TL based on the alignment of its scales with constructs identified by Hoggan's meta-analysis of TL research. In this article, we summarize the theoretical crosswalk between Hoggan and the BEVI, offer statistical evidence of construct validity for the BEVI as a measure of TL, and provide guidance for interpreting TL scores. We discuss implications of this methodology for higher education as well as other adult learning contexts such as mental health and wellness.